Analisis Kualitas Pelayanan Transportasi Laut (Survei pada Perusahaan Pelayaran di Pelabuhan Tanjung Priok, 2015) - Sumardi Sumardi (Sekolah Tinggi Maritim Yogyakarta, 2020)
This research aimed to analyzed ofservice quality os sea transportation on shipping company at The Port of Tanjung Priok, Jakarta. This research used SERVQUAL method. The purpose of SERVQUAL is to measure the five dimensions of service quality, that is: tangible, reliability, responsiveness, assurance, and empathy and based on gap analysis between expectation and service performance. This research using instrument in questionnaire form with involved 91 shipping company taken by simple random sampling technique. The research data analyzed Servqual. The result of this research show that in generally the service performance at at The Port of Tanjung Priok Jakarta perceived shipping companies is good enough and the level of expectation is high. The service dimension that perceived most important by shipping companies is reliability, followed by tangible, responsiveness, assurance and empathy. To improving service quality for shipping companies, then need to do the service improvement with priority order start from tangible, reliability, responsiveness, assurance, and empathy. The improvement effort also need refer to cartesius diagram, that is with trying to defense the service attributes in B quadrant, enhanced service attributes in A quadrant, and minimize the effort that doing on service attributes in C quadrant. Beside that, need to do the next research about service quality with using another service quality dimensions, such as 7S from McKinsey that analyzed by using qualitative approach.